Opposing regulation of endolysosomal pathways by long-acting nanoformulated antiretroviral therapy and HIV-1 in human macrophages - Araínga, Mariluz (Retrovirology, 2015)
BACKGROUND: Long-acting nanoformulated antiretroviral therapy (nanoART) is designed to improve patient regimen adherence, reduce systemic drug toxicities, and facilitate clearance of human immunodeficiency virus type one (HIV-1) infection. While nanoART establishes drug depots within recycling and late monocyte-macrophage endosomes, whether or not this provides a strategic advantage towards viral elimination has not been elucidated. RESULTS: We applied quantitative SWATH-MS proteomics and cell profiling to nanoparticle atazanavir (nanoATV)-treated and HIV-1 infected human monocyte-derived macrophages (MDM). Native ATV and uninfected cells served as controls. Both HIV-1 and nanoATV engaged endolysosomal trafficking for assembly and depot formation, respectively. Notably, the pathways were deregulated in opposing manners by the virus and the nanoATV, likely by viral clearance. Paired-sample z-scores, of the proteomic data sets, showed up- and down- regulation of Rab-linked endolysosomal proteins. NanoART and native ATV treated uninfected cells showed limited effects. The data was confirmed by Western blot. DAVID and KEGG bioinformatics analyses of proteomic data showed relationships between secretory, mobility and phagocytic cell functions and virus and particle trafficking. CONCLUSIONS: We posit that modulation of endolysosomal pathways by antiretroviral nanoparticles provides a strategic path to combat HIV infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12977-014-0133-5) contains supplementary material, which is available to authorized users.